The Schur Multiplicative and Harmonic Convexities for Three Classes of Symmetric Functions - Ming-bao Sun; Xin-ping Li; Ying-hui Zhang; Zai-yuan Zhang (Journal of Function Spaces)
We investigate the Schur harmonic convexity for two classes of symmetric functions and the Schur multiplicative convexity for a class of symmetric functions by using a new method and generalizing previous result. As applications, we establish some inequalities by use of the theory of majorization, in particular, and we give some new geometric inequalities in the n-dimensional space.